ISOLATION, CHARACTERIZATION AND DETERMINATON OF ANTIBACTERIAL ACTIVITY OF BACTERIAL AND FUNGAL ENDOPHYTES FROM OCIMUM SANCTUM AND PHYTOCHEMICAL ANALYSIS - SUMAN SHEKHAWAT; GAURAV SHAH (International Journal of Pharma and Bio Sciences, 2013)
A study was carried out to isolate endophytes from Ocimum sanctum (Tulsi) and check their anti-bacterial activitiy against Escherichia coli, Bacillus megaterium, Pseudomonas aeruginosa, Serratia marsences, Bacillus subtilis, Staphylococcus aureus, Micrococcus luteus, Salmonella typhi, Salmonella typhi A and Salmonella typhi B. Nine endophytes were isolated including five fungal and four bacterial endophytes and they were found to inhibit the test organisms significantly. Extracellular enzyme production was also assayed and 88.8% of total isolates were found positive for cellulase, 77.7% isolates were positive for pectinase, 55.5% isolates were positive for amylase and 77.7% were positive for tyrosinase. Ethyl acetate extract from fungal isolates were subjected to phytochemical analysis and they showed positive results for presence of alkaloid and flavonoid. These results suggest that endophytes from tulsi are potential to be used as antimicrobial agents and for production of enzymes as well as secondary metabolites.